2016
DOI: 10.1007/s13197-016-2445-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of electrolyzed water on reducing the microbial populations on commercial mung bean sprouts

Abstract: The efficacy of acidic electrolyzed water (AEW) for reducing total bacteria, coliforms, yeast and mold counts on commercial mung bean sprouts was investigated. The impact of pH, available chlorine concentration (ACC) and the cleaning method on antimicrobial efficacy of AEW was studied. AEW with a pH of 4.47 reduced the total bacterial, coliform, and yeast and mold counts on mung bean sprouts by 1.23, 1.42 and 1.25 log CFU/g, respectively. The efficacy of AEW increased with increasing ACC, and further studies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Most importantly, AEW treatment showed a strong decontamination efficacy compared to the conventional industry practice. The antimicrobial activity of EW treatment could be attributed to the presence of inorganic oxidants, free reactive chlorine in the form of hypochlorous acid (HClO), ClO – , and Cl 2 , as well as high ORP (Park et al ., 2004; Liu & Yu, 2017). Previous study showed a high level of correlation between HOCl concentration and the bactericidal efficacy ( r = 0.95) of EW (Len et al ., 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, AEW treatment showed a strong decontamination efficacy compared to the conventional industry practice. The antimicrobial activity of EW treatment could be attributed to the presence of inorganic oxidants, free reactive chlorine in the form of hypochlorous acid (HClO), ClO – , and Cl 2 , as well as high ORP (Park et al ., 2004; Liu & Yu, 2017). Previous study showed a high level of correlation between HOCl concentration and the bactericidal efficacy ( r = 0.95) of EW (Len et al ., 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Various studies in which for the application of acidic EW was tested showed the inactivation of various microorganisms during the postharvest handling of mung bean sprouts (Liu & Yu, 2017), broccoli sprouts (Puligundla et al., 2018), and longan fruits (Chen, Xie, et al., 2020). According to Chen, Xie, et al.…”
Section: Impact Of Activated Water Systems On Spoilage and Microbial ...mentioning
confidence: 99%
“…According to Chen, Xie, et al (2020), the acidic EW treatment enhanced the fruit disease resistance through promoting the activities of some disease-resistant enzymes, boosted H 2 O 2 content, increased the activities of antioxidant enzymes, and maintained high levels of nonenzymatic antioxidant systems. Liu and Yu (2017) associated the effectiveness of acidic EW with higher ACC and lower pH.…”
Section: Electrolyzed Watermentioning
confidence: 99%
“…Kim et al (2003) [60] suggested that electrolyzed oxidizing (EO) water reduced initial Salmonella population in alfalfa seeds and sprouts. AEW reduced the total bacterial, coliform, yeast and mold counts on mung bean sprouts (Liu and Yu, 2016) [61] . Muller et al (2003) [62] reported that EO water is a viable option for controlling powdery mildew on gerbera daisies and provides growers an additional tool to reduce the use of traditional fungicides in greenhouses.…”
Section: Effect Of Electrolyzed Water On Seed Decontamination and Seed Qualitymentioning
confidence: 99%